Nucleação escolar e reorganização espacial da educação de jovens e adultos em Mamanguape/PB e Cuité de Mamanguape/PB: um estudo no campo da geografia da educação - Quintão, Altemar de Figueirêdo Bustorff (2023)
In this study, our objective was to analyze the implications of the school nucleation process in Mamanguape and Cuité de Mamanguape for students in Youth and Adult Education (EJA), within the field of Geography of Education. To do so, we conducted a qualitative-quantitative research, historically addressing public policies related to EJA. Additionally, we explored the debate on Geography of Education, which gave significant meaning to our work, as we dealt with a geographical study about an educational theme. From this field of knowledge, we investigated the nucleation process, understood as a reflection of the neoliberal doctrine of capitalism, in the mentioned municipalities. We analyzed the justifications presented by municipal governments that led to the implementation of closing EJA classes and providing school transportation for students to be taken to the new school (nucleus). Next, we identified three common challenges faced by EJA students when studying in nucleus schools and sought to relate them to our research area based on theoretical references. These challenges include: the increased time spent traveling to and from the nucleus school compared to studying in their own community; fear of violence when having to travel to a distant school different from what they were previously accustomed to; and finally, difficulties in accessing these nucleus schools, particularly related to road conditions and school transportation. We used a questionnaire, answered by eight participants who fit the research criteria, selected after analyzing various data related to EJA dropout rates between 2015 and 2019, prior to the COVID-19 pandemic in Brazil. The research participants were residents of one of the two municipalities in question, with four from the rural area of Cuité de Mamanguape and four from the urban outskirts of Mamanguape. These locations witnessed the closure of EJA classes. In order to continue their studies, they had to enroll in one of the four nucleus schools located in the central area of the urban zone in both municipalities. However, despite their efforts to overcome access challenges, they ended up abandoning these schools. These individuals agreed to report how the previously mentioned challenges were significant in their decision to drop out of school. As a result, we considered that each student experienced a specific reality, and the difficulties they faced were determining factors in their decisions. By cross-referencing theoretical data with the provided responses, we were able to ascertain that nucleation in EJA, combined with other problems, contributed to an increase in the school dropout rate, resulting in a decrease in educational attainment in the municipalities in question. As a consequence of this process, the economically disadvantaged population became even more vulnerable in the job market.